High-fidelity bilateral teleoperation system - Lim, Skyler Tze Shan (Nanyang Technological University, 2024)
Robots are capable of assisting disaster response tasks such as scouting and transporting supplies. In these highly uncertain and complex disaster zones, robotic teleoperation by a human operator has benefits over autonomous robots. In particular, bilateral teleoperation holds immense potential in disaster response by allowing force feedback to the operator. However, current bilateral teleoperation devices are not suitable for disaster response use, due to limitations in force and size. Therefore, this project aims to design a bilateral teleoperation manipulator system for use in disaster response. A 3 degree-of-freedom robot arm was developed using high torque motors and a cable system. The arm was then prototyped and constructed out of acrylic. Finally, the bilateral teleoperation was tuned using a simple control formula. Subsequently, minimal position and force errors were recorded between the master and slave device during teleoperation. While this project acts as a starting point to the arm development, future projects can aim to improve both the strength and control of the system. Doing so will contribute to the development of a more effective and viable disaster response bilateral teleoperation system.